MENGIDENTIFIKASI PERAN TEORI DAN KARAKTERISTIK PERUSAHAAN YANG DAPAT MEMPENGARUHI PENGUNGKAPAN CSR - Nufaisa Nufaisa; Binti Shofiatul Jannah (Behavioral Accounting Journal, 2020)
Corporate Social Responsibility (CSR) is a part of corporate business social activities as an effort to bring good impact on environmental issues. Information regarding social activities, both economic also non-economic, has attracted the attention of users of financial reports. The disclosure of corporate social responsibility to the public is still voluntary. The theoretical development of CSR is stakeholder theory and legitimacy theory. Both of these theories come from a political economy perspective which explains the motivation for social disclosure. Stakeholder theory try to clarify the credentials of stakeholders. Meanwhile, the legitimacy theory explains that voluntary disclosure is component of the legitimacy process. The disclosure of corporate social responsibility can also be influenced by company characteristics, such as firm size, profitability, company profile, the number of the board of commissioners, leverage, ownership structure, business age, company size, growth and industrial type. This paper aims to explain the motivation for CSR disclosure from a theoretical perspective and identify company characteristics that can influence CSR disclosure.